Protection of Unregistered Well-Known Trademarks: The Bangladeshi Trademarks Regime Revisited - Islam, Mohammad Towhidul; Mamun, Md Jahid Al (Dhaka University Law Journal, 2022)
Abstract not available Dhaka University Law Journal, Vol. 32(2), 2021 P.15-48